Ключові етапи адаптації acquis communautaire до правової системи України: історичний огляд - Расторгуєва, Н. О.; Rastorhuieva, N. O. (ScienceRise: Juridical Science. - 2024. - № 2 (28). - P. 12-21, 2024)
Метою статті є історичний огляд ключових етапів адаптації законодавства України до acquis communautaire. Визначено основні напрями адаптації внутрішнього законодавства України з acquis Європейського Союзу. Запропоновано шляхи узгодження нормативно-правових актів України у відповідність з acquis communautaire.

The article is aimed at clarifying the status of regulatory and legal support for the process of adaptation of the national legislation to the acquis communautaire. It is stated that the Ukrainian state has already completed most of the steps to join the EU. Attention is focused on the relevance of the study, which is due to Ukraine's officially obtaining the EU candidate status and the transition to the negotiation process between the EU and Ukraine on the latter's accession to the EU. The author analyses the provisions of Ukrainian legislation and scientific research on the understanding of the concept of ‘acquis communautaire’. The author's definition of this legal phenomenon is formulated, which should be understood as the sources of EU law, standards, principles of external and internal activities and other achievements of the European Communities. The author's own approach to distinguishing four stages of adaptation of the national legislation to the acquis communautaire in chronological order is proposed. The first stage was when Ukrainian legislation implemented the EU norms and standards to establish economic cooperation between Ukraine and the EU in various areas for the development of various relations between the partners. The second stage was a testament to the irresistible desire of Ukraine and Ukrainians to be part of the EU community and contributed to the signing and entry into force of the EU-Ukraine Association Agreement. The third stage demonstrates Ukraine's path from the signing of the EU-Ukraine Association Agreement to the EU candidate status. The fourth stage is connected with the European Council's announcement of the start of negotiations with Ukraine on the country's accession to the EU and the need for comprehensive harmonisation and adaptation of Ukrainian legislation to the EU acquis in connection with the prospect of EU membership. It is emphasised that the implementation of the acquis communautaire into the national legal system should pursue national interests and be a political, economic, legal and social consensus on key issues of European integration transformations.

Целью статьи является историческое обозрение ключевых этапов адаптации законодательства Украины к acquis communautaire. Определены основные направления адаптации внутреннего законодательства Украины к acquis Европейского Союза. Предложены пути согласования нормативно-правовых актов Украины в соответствие с acquis communautaire.
Keywords: acquis communautaire; acquis ЄС; адаптація законодавства; євроінтеграція; Європейський Союз; правова система України; EU ‘acquis’; adaptation of legislation; European integration; European Union; legal system of Ukraine; acquis ЕС; адаптация законодательств; европейская интеграция; Европейский Союз; правовая система Украины